From the Asphalt to the Forest: Cia. Livre’s research on the creation of an epic and perspectivist scenic language - Romano, Lúcia Regina Vieira [UNESP] (Universidade Federal do Rio Grande do Sul, 2021)
This article examines Cia. Livre’s scene, which questions the constitution of Brazilian identity, relating the individual in the urban context and Amerindian thought. Since the performance Vem Vai, o caminho dos mortos (2007), transit between the forest and the asphalt has been identified, instituted in the scenic translations of anthropophagy, according to Andrade (1928), Campos (1992), and Nunes (1979), and Amazonian cosmology, based on theories of perspectivism, especially Descola (1992), Carneiro da Cunha (1998), Kopenawa and Albert (2015), and Viveiros de Castro (1996; 2002; 2015). It concludes by highlighting the company’s decolonial strategy in the use of anthropology in order to imagine other humanities.

Cet article examine la scène de Cia. Livre, qui problématise la constitution de l'identité brésilienne, mettant en relation l'individu dans le contexte urbain et la pensée amérindienne. Depuis le spectacle Vem Vai, le chemin des morts (2007), un transit entre la forêt et l'asphalte a été établi, institué dans la traduction scénique de l'anthropophagie, selon Andrade (1928), Campos (1992) et Nunes (1979), et la cosmologie amazonienne, basée sur les théories du perspectivisme, en particulier Descola (1992), Carneiro da Cunha (1998), Kopenawa e Albert (2015) et Viveiros de Castro (1996; 2002; 2015). Il conclut en mettant en évidence la stratégie décoloniale de la compagnie dans l'utilisation de l'anthropologie, pour imaginer d'autres humanités.
De l’Asphalte à la Forêt: les recherches de Cia. Livre sur la création d'une scène épique et perspectiviste
Keywords: Contemporary Scene; Brazilian Theater; Epicization Processes; Amerindian Perspectivism; Contemporary Anthropology